New Objects, Not New Features, Trigger the Attentional Blink - Raymond, Jane E. (Psychological Science, 2003)
When two different targets must be selected from a rapid serial visual presentation (RSVP) of images, perception of the second target will be markedly reduced if it is presented within about a half second of the first. Known as the attentional blink (AB), this effect reflects temporal limitations in attentional processes enabling awareness of image representations. I tested whether these limitations occur at an object or feature level of processing by presenting (in RSVP) multiple images of the same (old) object depicted in different orientations. Targets were defined by new features added either to this or to a new object. When the first target feature appeared on the old object, no AB effects were found even when the second target was a new object. When a new object carried the first target feature, an AB effect was found even when the second target feature appeared on the same "new" object. The AB appears to reflect limitations in the creation of new object representations, rather than temporal limitations of awareness per se.